Siphon-type hydroelectric plants: application for power generation in a low head dam in southern Brazil - Janaina Terhorst Pizutti; Carlos Henrique Pereira Assunção Galdino; Fernando Setembrino Cruz Meirelles; Alexandre Beluco (The Journal of Engineering and Exact Sciences)
Hydroelectric energy continues to be the most representative renewable resource in the world, accounting today for 40% of installed capacity. The availability of water, combined with the technologies for generating electricity at a reasonable cost, have sustained the success of this type of generation over the years. Continuing to leverage the hydroelectric sector is even more challenging today, because there is a growing world demand for energy, at the same time that the most attractive places from an economic point of view have already been benefited. The current context refers to approaches to water exploitation aimed at exploiting smaller-scale potentials and existing water structures that operate in a multifunctional way. Solidified in this conjecture, the purpose of this study is to contribute, in the sense of attributing alternatives, for the generation of energy in existing low head dams through the pre-dimensioning of a siphon plant. This type of plant is part of a specific and still evolving niche for decentralized power generation. The reduced structural requirements (generator, turbine, and suction tube), as well as the minimal intervention in the existing structure of the dam, the cessation of new socio-environmental and economic impacts related to the construction of a new plant are the main favorable characteristics of these facilities. The case study of an inoperative plant and the tools available in the Homer Software for data simulation were used as methodological resources. Two base configurations were considered: one with 100% renewable matrices and another one including a diesel generator. From them, different hybrid systems, to determine an optimal configuration in terms of net present cost, were simulated. Among the simulations performed, the most promising optimal solution was hybrid, considering among its components a set of siphon turbines totaling 271 kW, plus 50 kW in photovoltaic modules and 140 kW in a diesel support system. A battery bank with 32 200 Ah batteries complemented this system. The energy cost for this system is $0.164 per kWh. For a system without diesel and with 0% service failures, viable results appear only up to 2600 kWh load.